Determination of the Dirichlet condition in an electrodynamic problem describing the anyzotropically conductive medium - Kleiza, Vytautas; Sėrikovienė, Silvija (Lietuvos matematikos rinkinys, 2002)
The paper deals with the problem of potential determination on a plain domain, using the conformal mapping theory.